The Influence of Educational Media on the Perception and Motivation of Adolescent Girls in Consuming Iron Supplement Tablets - Agiesna; Kurniasari, Ratih (JURNAL KESMAS DAN GIZI (JKG), 2025)
Menarche in teenage girls may increase their risk of anemia relative to boys in the same age category. This research was carried out to explore how educational media affects adolescent girls' perceptions and motivation concerning the use of iron-supplement tablets. The study used a quasi-experimental design, implementing a one-group pretest and post-test method without a control group. Sample selection was conducted via purposive sampling, and data collection utilized questionnaires aimed at evaluating adolescent girls' perceptions and motivations. After the preliminary pretest, an intervention was implemented that featured printed standing banners and digital content, such as videos and digital scrapbooks. Data analysis included employing the paired t-test to detect any variations in perception and motivation prior to and following the media intervention. The outcomes of the statistical analyses showed a notable shift in perception and motivation after exposure to printed standing banner media (p < 0.05). Nevertheless, no notable changes were detected following the interventions of digital video and digital scrapbook media (p ≥ 0.05). The research finds that printed media significantly influences adolescent girls' views and motivation to take iron-supplement tablets more than digital media does.